2002
DOI: 10.1046/j.1344-3941.2002.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intracerebroventricular infusion of urocortin on feed and salt intake in parotid fistulated sheep

Abstract: The effect of a new peptide, brain urocortin (UCN), in the central regulation of feed and salt intake in parotid fistulated sheep was investigated through a continuous intracerebroventricular (ICV) infusion of the peptide at a small dose for 48 h. Feed and salt intake on day 1 of UCN infusion were similar to those before infusion. However, feed and salt intake on day 2 during UCN infusion decreased significantly. Water intake on days 1 and 2 during UCN infusion was the same as that before infusion. Saliva secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The results were that saliva secretion from the unilateral parotid fistula and feed intake during the morning 2 h feeding period in the infusion treatment (828±131.7 ml/2 h; 1,100±544.1 g/2 h) were significantly greater compared to the non infusion treatment whereby saliva secretion was 399±50.7 ml/2 h and feed intake was 489±185.0 g/2 h. The feed intake in goats with a parotid fistula that were intraruminally infused with saliva,was similar to pre-fistulation values (929±81.8 g/ 2 h) (Sunagawa et al, 2002a). Sunagawa et al (2002b) reported that in an experiment using a pedal press system for the delivery of water and salt, feed intake of alfalfa chaff in non-fistulated sheep was significantly greater than nonintraruminally infused fistulated sheep. Therefore, it is thought that the internal environment of animals maintained with a daily infusion of parotid saliva in the present experiment was similar to non-fistulated animals.…”
Section: Discussionmentioning
confidence: 67%
“…The results were that saliva secretion from the unilateral parotid fistula and feed intake during the morning 2 h feeding period in the infusion treatment (828±131.7 ml/2 h; 1,100±544.1 g/2 h) were significantly greater compared to the non infusion treatment whereby saliva secretion was 399±50.7 ml/2 h and feed intake was 489±185.0 g/2 h. The feed intake in goats with a parotid fistula that were intraruminally infused with saliva,was similar to pre-fistulation values (929±81.8 g/ 2 h) (Sunagawa et al, 2002a). Sunagawa et al (2002b) reported that in an experiment using a pedal press system for the delivery of water and salt, feed intake of alfalfa chaff in non-fistulated sheep was significantly greater than nonintraruminally infused fistulated sheep. Therefore, it is thought that the internal environment of animals maintained with a daily infusion of parotid saliva in the present experiment was similar to non-fistulated animals.…”
Section: Discussionmentioning
confidence: 67%
“…Saliva is continuously lost in parotid fistulated sheep. Despite sheep being trained on a pedal-press system to allow them free access to a 0.6 mol/L NaHCO 3 solution and water, so long as the saliva lost through the parotid fistula was not returned to the rumen, sodium and water appetite in the fistulated sheep markedly increased while feed intake and urine volumes decreased (Sunagawa et al, 2002a). In the present experiment, in order to avoid any harmful influences on the animals, the saliva collected from the parotid fistula throughout the previous day was infused with a bathtub pump via an extension tube into the rumen prior to morning feeding.…”
Section: Blairmentioning
confidence: 99%
“…Silanikove and Tadmor (1989) reported that in cows deprived of water for long periods of time, there was a positive relationship between saliva secretion rates and wheat hay intake. Sunagawa et al (2002b) reported that despite being given free access to water and salt via a pedal press system, sheep with a parotid fistula consumed substantially less alfalfa chaff than sheep without a parotid fistula. It is therefore thought that saliva secretion volume is a regulating factor in dry forage intake.…”
Section: Introductionmentioning
confidence: 99%